IMPLEMENTASI PERATURAN PRESIDEN NOMOR 125 TAHUN 2016 TENTANG PENANGANAN PENGUNGSI DARI LUAR NEGERI DI PEKANBARU - Teguh Pratama Akmal; Irwan Iskandar (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
Indonesia is not a country that has ratified the 1951 Refugee Convention so that foreign refugees who are living in Indonesia are overwhelmed in following the rules of the refugee convention. So various regulations were made to deal with foreign refugees, especially Presidential Regulation Number 125 of 2016 concerning the handling of foreign refugees, Then the question arises about how the Presidential Regulation Number 125 of 2016 regarding the handling of foreign refugees is raised in Pekanbaru.This study uses a pluralism perspective where policies can be from different actors and uses international organization theory. The method used is descriptive qualitative method with data collection using open interview studies, direct observation studies to the research site and documentation studies from articles, journals, and sites on the InternetThis research shows that the implementation of Presidential Regulation number 125 of 2016 concerning The Handling of foreign refugees in Pekanbaru as the basis for the main rules that apply in terms of handling the foreign refugees in Pekanbaru is carried out well following every point in the articles contained in this Presidential Regulation. The handling of foreign refugees that is implemented in Pekanbaru is divided into 1) Finding foreigners who are seeking asylum, 2) Temporary shelter and providing facilities and services during the temporary shelter process in Indonesia, 3) Immigration security and supervision while temporarily living in the area. Republic of Indonesia, especially Pekanbaru. Keywords:Implementation, Presidential Regulation, Pekanbaru, Refugees.